Approach for paediatric cervical lymphadenopathy: Tuberculosis versus lymphoma (Bangladesh Journal of Medical Science, 2019)
Constitutional symptoms are the most common clinical manifestation of the systemic disease. When there is the presence of cervical lymphadenopathy concurrently, systemic infection or malignancy has to be taken into consideration. At the paediatric or adolescent age group, tuberculosis and lymphoma are the common diseases that associated with these symptoms. We should consider patient’s age group, risk factors and the disease presentation for the diagnosis. With the guidance of the imaging studies, laboratory and histopathological studies, the precise final diagnosis is made.Bangladesh Journal of Medical Science Vol.18(1) 2019 p.149-152